The Effect Of Good Corporate Governance Structure On Financial Distress (Study On The Automotive Industry Sector And Its Components Listed On The Indonesia Stock Exchange For The 2014-2019 Period) - Yusmaniarti, Yusmaniarti; Astuti, Budi; Marini, Marini; Setiorini, Hesti; Khair, Ummul; Rambe, Siti Fatimah (BIMA Journal (Business, Management, & Accounting Journal), 2022)
This study aims to determine the effect of managerial ownership, institutional ownership, independent commissioners and audit committees on financial distress in companies in the automotive industry sector and their components listed on the Indonesia Stock Exchange for the 2014-2019 period. The sample used was 7 companies in the automotive industry sector and their components listed on the Indonesia Stock Exchange with the number of observations during the 2014-2019 period so that the total research data was 42. The sampling technique used purposive sampling. Analysis of the data used is multiple linear regression. The results showed that managerial ownership had an effect on financial distress. Institutional ownership has an effect on financial distress. Independent commissioners have an effect on financial distress. The audit committee has an effect on financial distress. Managerial ownership, institutional ownership, independent commissioners and audit committees have a joint effect on the financial distress of companies in the Automotive Industry Sector and its Components Listed on the Indonesia Stock Exchange for the 2014 â€“ 2019 period.Â